2002
DOI: 10.1267/ahc.35.11
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Inducible Nitric Oxide Synthase, Interleukin-1.BETA., and Interleukin-1 Receptor in the Temporomandibular Joint of Normal Rats.

Abstract: Nitric oxide (NO) is generated from Larginine by NO synthase (NOS) and has multiple functions under both physiological and pathological conditions. One isoform of NOS, inducible NOS (iNOS) is expressed in the cells such as macrophages after induction with various cytokines or mechanical stress. In this study, we investigated the distribution of iNOS, interleukin-1, (IL-1,) and its receptor, the IL-1 receptor (IL-1R), in the synovial membrane of the temporomandibular joint (TMJ) of normal rats using immunolight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 40 publications
(58 reference statements)
1
11
0
Order By: Relevance
“…Immunoelectron microscopy has revealed that immunoreactive iNOS is found in both synoviocytes type A (macrophage-like) and B (fibroblast-like) [45]. NO may play an important role in the physiological maintenance of the TMJ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoelectron microscopy has revealed that immunoreactive iNOS is found in both synoviocytes type A (macrophage-like) and B (fibroblast-like) [45]. NO may play an important role in the physiological maintenance of the TMJ.…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that iNOS was present in the articular disc, the articular cartilage chondrocytes, and the synovial cells of the rat TMJ under physiological conditions. Immunoelectron microscopy has revealed that immunoreactive iNOS is found in both synoviocytes type A (macrophage-like) and B (fibroblast-like) [ 45 ]. NO may play an important role in the physiological maintenance of the TMJ.…”
Section: Discussionmentioning
confidence: 99%
“…Specimens were prepared for immunohistochemistry followed by light microscopy according to the methods described in our previous reports [21,48,49]. Briefly, gingival specimens were immersed overnight in 0.1 M PB containing 20% sucrose at 4°C.…”
Section: Immunohistochemistry and Light Microscopymentioning
confidence: 99%
“…Immunohistochemistry was based on the avidin-biotinperoxidase complex (ABC) method (ABC Kit; Vector Laboratories, Burlingame, CA, USA) as described previously [21,48,49]. Immunohistochemistry was carried out at room temperature (RT).…”
Section: Immunohistochemistry and Light Microscopymentioning
confidence: 99%
See 1 more Smart Citation